Transcriptional corepressor activity of CtBP1 is regulated by ISG15 modification - Yun Hwan Lim; Yoon Jin Park; Jieun Lee; Jung Hwa Kim (Animal Cells and Systems)
C-terminal binding protein 1 (CtBP1) is a critical transcriptional corepressor of many tumor suppressor genes and plays diverse roles in the progression of cancers. The transcriptional repression function of CtBP1 is mediated by recruiting histone-modifying enzymes, such as histone deacetylases and histone methyltransferases, to target genes by binding with DNA-interacting factors. Several post-translational modifications of CtBP1 have been identified, including ubiquitination, phosphorylation, and SUMOylation. This paper reports that CtBP1 is conjugated by ISG15. Endogenous CtBP1 was modified by ISG15 after interferon-α treatment in HeLa cells. The ISGylation process of CtBP1 was regulated by deISGylation enzyme USP18 and ISG15 E3 ligase EFP. Interestingly, CtBP1 ISGylation affected the binding affinity between CtBP1 and some components of CtBP1-associated transcriptional complexes. HDAC1 and LSD1 bound more efficiently to ISG15-conjugated CtBP1 than non-conjugated CtBP1. On the other hand, binding between CtBP1 and HDAC4 was unaffected by ISG15 modification. Furthermore, ISG15 modification enhanced the transcriptional repression activity of CtBP1 on several target genes related to EMT and apoptosis. These findings suggest that the ISG15 modification of CtBP1 modulates the function and activity of CtBP1 and that CtBP1 ISGylation may provide a new insight for CtBP1-mediated cancers.